Tax Socialization, Tax Knowledge, and Tax Sanctions' Influence on Taxpayer Compliance with Individuals at KPP Pratama Pekalongan - Mochamad Yusuf; Imahda Khoiri Furqon; Drajat Stiawan (Universitas Pamulang, 2022)
The number of taxpayers from year to year is increasing. However, the increase in the number of taxpayers is not matched by taxpayer compliance in paying taxes. The problem of compliance is an obstacle to maximising tax revenue. The purpose of this study was to examine the effect of Tax Socialization, Tax Knowledge, and Tax Sanctions on Individual Taxpayer Compliance at the Pekalongan Pratama Tax Service Office. The sample used was 100 respondents from the population of Individual Taxpayers registered in Pekalongan 17.261 in 2020. Not all of these numbers became the research object for time and cost-efficiency. Sampling was done by a simple random sampling method. The primary data collection method used is a survey method using a questionnaire. Data were analyzed using instrument tests, classical assumption analyses, multiple linear regression analyses, and hypothesis testing. The results of the analysis carried out on individual taxpayers registered at KPP Pratama Pekalongan, namely the variables of Tax Socialization and Tax Sanctions affect the Compliance of Individual Taxpayers. However, Tax Knowledge has no effect on Individual Taxpayer Compliance